What Factors Affecting Indonesian Mining Companies’ Stock Price Before and During the COVID-19 Pandemic - Ulfiani, Nurin; Simon, Zainal Zawir; Nasution, Ananta Hagabean (Lembaga Penelitian Universitas YARSI, 2024)
This study aims to analyze the factors influencing stock prices of mining sector companies listed on the Indonesian Stock Exchange before and during the COVID-19 pandemic. Panel data regression is utilized, with a sample of 39 mining companies selected through Purposive Sampling. Results indicate that, before the pandemic (2017–2019), company size significantly impacted stock prices, while liquidity, leverage, and profitability ratios did not. Conversely, during the pandemic (2020–2022), liquidity ratios and company size had a significant effect on stock prices, unlike leverage and profitability ratios. Throughout both periods, stock prices were significantly affected by liquidity, leverage, profitability, and company size. These findings provide insights for businesses to enhance productivity and financial sustainability, especially during economic instability like the pandemic. They also serve as indicators for investors regarding buying or selling shares, particularly in the mining sector. Additionally, the government can leverage these insights to optimize the mining sector, potentially boosting company revenues and supporting GDP growth.